Dynamics of Productive Zakat Implementation in Empowering MSMEs Mustahik: A Case Study of BAZNAS Palangka Raya City - Amanda Nur Fatimah; Rofi'i; Arif Mubarok (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Productive zakat is an important instrument in empowering Micro, Small, and Medium Enterprises (MSMEs), especially for those entitled to receive aid (mustahik) who face limitations in capital, business facilities, and managerial capacity. However, at the local level, the implementation of the productive zakat program still faces various institutional and operational challenges. This study aims to analyze the dynamics of productive zakat implementation in empowering MSMEs entitled to receive aid through a case study of BAZNAS Palangka Raya City. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews with BAZNAS managers and beneficiary mustahik, supported by field observations and document analysis. The results show that the implementation of productive zakat in Palangka Raya City is mostly realized through the provision of productive assets, such as business carts, Z-Mart facilities, and MSME tents, which contribute to increasing productive activities and initial income of mustahik. However, program implementation still faces obstacles such as limited human resources, uneven mentoring, and weak post-assistance monitoring, which impacts the sustainability of MSME development. These findings indicate that the implementation of productive zakat still tends to be asset-based and has not been fully integrated with sustainable mentoring and capacity-building mechanisms. Therefore, strengthening institutional capacity and implementing a more comprehensive empowerment approach are crucial to increasing the effectiveness and sustainability of productive zakat programs at the local level